The Role of Folic Acid in Stroke Prevention - Anditya Almanda Zefanya, Alvin; Dela Pebrianti, Mariska (Rifa'Institute, 2021)
Stroke is one of the most serious health problems faced today. This is because a sudden stroke can cause physical and mental disabilities that can interfere with a person's productivity and can even cause sudden death. Stroke can be divided into two, namely hemorrhagic stroke and non-hemorrhagic stroke. Hemorrhagic stroke is a stroke that occurs due to damage to blood vessels in the brain. While non-hemorrhagic stroke, also known as ischemic stroke, occurs when the blood supply to the brain is interrupted or stopped. About 80% of the most common strokes are caused by an ischemic stroke. One of the causes of ischemic stroke due to atherosclerotic plaque. Elevated levels of homocysteine ??in the blood (hyperhomocysteinemia) can lead to chronic inflammation of the blood vessels that triggers the formation of atherosclerotic plaques and causes blockage of blood flow. Folic acid is a type of water-soluble vitamin and can play a role in preventing stroke. Folic acid can act as an antihomocysteine ??so that it can prevent the formation of atherosclerotic plaques which is one of the risk factors for stroke